Characterization of MdMYB68, a suberin master regulator in russeted apples - Xu, Xuan; Guerriero, Gea; Domergue, Frederic; Beine-Golovchuk, Olga; Cocco, Emmanuelle; Berni, Roberto; Sergeant, Kjell; Hausman, Jean-Francois; Legay, Sylvain (Frontiers in Plant Science, 2023)
Introduction Apple russeting is mainly due to the accumulation of suberin in the cell wall in response to defects and damages in the cuticle layer. Over the last decades, massive efforts have been done to better understand the complex interplay between pathways involved in the suberization process in model plants. However, the regulation mechanisms which orchestrate this complex process are still under investigation. Our previous studies highlighted a number of transcription factor candidates from the Myeloblastosis (MYB) transcription factor family which might regulate suberization in russeted or suberized apple fruit skin. Among these, we identified MdMYB68, which was co-expressed with number of well-known key suberin biosynthesis genes. Method To validate the MdMYB68 function, we conducted an heterologous transient expression in Nicotiana benthamiana combined with whole gene expression profiling analysis (RNA-Seq), quantification of lipids and cell wall monosaccharides, and microscopy. Results MdMYB68 overexpression is able to trigger the expression of the whole suberin biosynthesis pathway. The lipid content analysis confirmed that MdMYB68 regulates the deposition of suberin in cell walls. Furthermore, we also investigated the alteration of the non-lipid cell wall components and showed that MdMYB68 triggers a massive modification of hemicelluloses and pectins. These results were finally supported by the microscopy. Discussion Once again, we demonstrated that the heterologous transient expression in N. benthamiana coupled with RNA-seq is a powerful and efficient tool to investigate the function of suberin related transcription factors. Here, we suggest MdMYB68 as a new regulator of the aliphatic and aromatic suberin deposition in apple fruit, and further describe, for the first time, rearrangements occurring in the carbohydrate cell wall matrix, preparing this suberin deposition.